PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN METODE PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING DENGAN METODE PEMBELAJARAN CERAMAH PADA MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI 4 PADANG - Yenti, Gusrida; S.Pd., M.Pd, Armiati; Susanti, S.Pd, Dessi (Pendidikan Ekonomi, 2014)
AbstrakThe background of this research is the lower of student economics result in the class XI SMA N 4 Padang, 2013 / 2014 period. This matter is caused by the lack of student activity in learning process. The aim of this research is to know how the Difference Result of Student learning by using study Co-Operative method of Student Facilitator and Explaining type with Discourse Method in SMA N 4 Padang. Based on data analysis result is found average value 73,26 for class experiment and 62,77 for class control. From data analysis result is known value of thitung = 2,978 that is bigger than value of ttabel = 1,67 meaning raised to be hypothesis to be accepted at real level Î± = 0,05. This matter indicate that there are significant difference between student learning result by using study co-operative method of student explaining and facilitator type with discourse method. Its mean that the result of student economics learning by using study co-operative method of Student Facilitator And Explaining type is better than discourse method at class XI SMA N 4 Padang.